Classification of systems of mobile learning - Мотін, Максим Миколайович (Eastern-European Journal of Enterprise Technologies, 2012)
The generalized description of the systems of the mobile controlled from distance education is Given, its basic advantages and defects are certain in the context of the use for educating An attempt over of classification of the mobile departmental teaching is brought